Electricity-powered artificial root nodule - Shengtao Lu (Nature Portfolio, 2020)
Root nodules are of key importance in nitrogen fixation. Here, the authors report on an electrically powered artificial root nodule for nitrogen fixation made from silicon-based microwires which can accommodate nitrogen fixing symbiotic bacteria for fixing nitrogen into biomass and free ammonia.